Bacterial analysis on dentistry and the study of antibacterial activity using formulated herbal toothpaste - Robert, Gabriel Amalan; Nagarajan, S. M. (International Multidisciplinary Research Journal, 2016)
The current investigation dealt with studies on isolation and identification of oral biofilm forming bacteria and using formulated herbal toothpaste for inhibition. In this study, the bacterial populations were observed, and three were isolated from the used denture and different toothbrushes from various persons. From the collected oral samples, the streptococci, staphylococci, and bacilli were isolated and confirmed by biochemical tests. The increasing awareness of the environment and healthy lifestyles are generating some demand for more natural products such as those containing herbal extracts, so some of the indigenous medicinal plants were identified and formulated as herbal toothpaste; the efficiency of herbal toothpaste in inhibiting the growth of periodontal bacteria were evaluated. The bacterial inhibition rate and culture turbidity were observed in using herbal toothpaste against isolated pathogenic oral bacteria. Results were discussed.